A comparative thermodynamic evaluation of bioethanol processing from wheat straw. (15th August 2018) - Hammond, Geoffrey P.; Mansell, Ross V.M.
Highlights: Alternative routes to sustainable biofuels from wheat straw have been appraised. Thermodynamic analysis has been employed to evaluate four bioethanol processes. The Net Energy Value of each production path or route was determined. Exergetic efficiencies were estimated for the different processes. Process improvement potentials were then calculated on a comparative basis. Abstract: The thermodynamic implications of different bioethanol production routes from wheat straw (a cellulosic co-product or 'waste' stream) have been evaluated. Comparative thermodynamic (energy and exergy) analysis gives rise to alternative insights into the relative performance of various process chains. Energy analysis of four different production paths were firstly analysed via the consideration of mechanical work, temperature changes and separating techniques. The Net Energy Value (NEV) of each production path or route was then evaluated, including the effect of system boundary expansion. In contrast, the thermodynamic property known as 'exergy' reflects the ability of undertake 'useful work', but does not represent well heating processes. Exergetic efficiencies were consequently obtained via chemical and physical exergy calculations, along with some of the electrical inputs to the different processes. The exergetic 'improvement potentials' of the process stages were then determined using the exergetic efficiencies and irreversibility values respectively. These estimates will enable industrialists and policy makers to take account of some of the ramifications of alternative bioethanol production routes in a low carbon future.